Late Miocene to Pliocene stratigraphy of the Kura Basin, a subbasin of the South Caspian Basin: implications for the diachroneity of stage boundaries. (10th May 2014) - Forte, Adam M.; Sumner, Dawn Y.; Cowgill, Eric; Stoica, Marius; Murtuzayev, Ibrahim; Kangarli, Talat; Elashvili, Mikheil; Godoladze, Tea; Javakhishvili, Zurab
Abstract Relative ages of late Cenozoic stratigraphy throughout the Caspian region are referenced to regional stages that are defined by changes in microfauna and associated extreme (>1000 m) variations in Caspian base level. However, the absolute ages of these stage boundaries may be significantly diachronous because many are based on the first occurrence of either transgressive or regressive facies, the temporal occurrence of which should depend on position within a basin. Here, we estimate the degree of diachroneity along the Akchagyl regional stage boundary within the Caspian basin system by presenting two late Miocene‐Pliocene aged measured sections, Sarica and Vashlovani, separated by 50 km and exposed within the Kura fold‐thrust belt in the interior of the Kura Basin. The Kura Basin is a western subbasin of the South Caspian Basin and the sections presented here are located >250 km from the modern Caspian coast. New U‐Pb detrital zircon ages from the Sarica section constrain the maximum depositional age for Productive Series strata, a lithostratigraphic package considered correlative with the 2–3 Myr‐long regional Eoakchagylian or Kimmerian stage that corresponds to a period of extremely low (>500 m below the modern level) Caspian base level. This new maximum depositional age from the Productive Series at Sarica of 2.5 ± 0.2 Ma indicates that the regionally extensive Akchagyl transgression, which ended the deposition of the Productive Series near the Caspian coast at 3.2 Ma, may have appeared a minimum of 0.5 Myr later in the northern interior of the Kura Basin than at the modern Caspian Sea coast. The results of this work have important implications for the tectonic and stratigraphic history of the region, suggesting that the initiation of the Plio‐Pleistocene Kura fold‐thrust belt may have not been as diachronous along strike as previously hypothesized. More generally, these results also provide a measure of the magnitude of diachroneity possible along sequence boundaries, particularly in isolated basins. Comparison of accumulation rates between units in the interior of the Kura subbasin and the South Caspian main basin suggest that extremely large variations in these rates within low‐stand deposits may be important in identifying the presence of subbasins in older stratigraphic packages.